Infective respiratory exacerbations in young adults with cystic fibrosis: role of viruses and atypical microorganisms. Issue 9 (September 1989) - Ong, E L; Ellis, M E; Webb, A K; Neal, K R; Dodd, M; Caul, E O; Burgess, S
Abstract : Thirty six adults with cystic fibrosis were studied over one year to determine the incidence of infection with respiratory viruses and atypical organisms. Nineteen patients entered the study during an acute exacerbation of respiratory symptoms with an increase in purulent sputum production, cough, or breathlessness accompanied by a fall in FEV1 (group 1); 17 patients entered when they were stable both clinically and in terms of lung function values (group 2). Group 1 patients had a mean of 2.6 (range 1-4) infective exacerbations during the year and group 2 patients a mean of 1.1 (0-2) exacerbations. Eleven patients developed serological evidence of viral (influenza virus A and B, cytomegalovirus, human rhinovirus 2, adenovirus) or Mycoplasma pneumoniae infection. There was no difference in seroconversion rates between group 1 (five patients) and group 2 (six patients). There was a weak association between viral seroconversion and the isolation of Pseudomonas aeruginosa from sputum, though this was not significant.